2017
DOI: 10.1161/strokeaha.117.018397
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Catheter Ventriculocisternostomy for Clearance of Subarachnoid Hemorrhage

Abstract: STX-VCS was feasible and safe in patients with severe aneurysmal subarachnoid hemorrhage. Initial results indicate that DCI and mortality can be reduced, and neurological outcome may be improved with this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Small trials of aSAH clearance via other direct clearance methods have shown decreased rates of DCI and improved outcomes. A small, matched cohort trial of direct cisternal lavage with urokinase with the objective of SAH clearance showed decreased rates of DCI and mortality with a trend towards decreased shunt dependence and improvement in functional outcomes at time of rehabilitation discharge [ 222 ]. The trial did not assess for efficacy of SAH clearance but mentioned that 9 of 20 patients with early CTs exhibited near complete resolution of SAH.…”
Section: Clinical Evidence Supporting Early and Total Evacuation/treatment Of Intracranial Hemorrhagementioning
confidence: 99%
“…Small trials of aSAH clearance via other direct clearance methods have shown decreased rates of DCI and improved outcomes. A small, matched cohort trial of direct cisternal lavage with urokinase with the objective of SAH clearance showed decreased rates of DCI and mortality with a trend towards decreased shunt dependence and improvement in functional outcomes at time of rehabilitation discharge [ 222 ]. The trial did not assess for efficacy of SAH clearance but mentioned that 9 of 20 patients with early CTs exhibited near complete resolution of SAH.…”
Section: Clinical Evidence Supporting Early and Total Evacuation/treatment Of Intracranial Hemorrhagementioning
confidence: 99%
“…A plethora of medical treatment options to attenuate vasospasm, such as statins, corticosteroids, clazosentan, milrinone, magnesium sulfate, fasudil hydrochloride, cilostazol and edaravone, has been tested in both, experimental and clinical settings; however, with exemption of one single agent, the calcium channel antagonist nimodipine, no systemic medical therapy has shown a robust and reproducible effect on functional outcome in these patients [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Therefore, in most centers, enteral administration of nimodipine is part of the standard treatment protocol in order to prevent vasospasm; however, different routes of administration including parenteral intravenous administration, intrathecal administration via external ventricular drainage and intracisternal administration via stereotactically placed catheters have been used and tested; yet, these alternative methods of administration remain to be of experimental character [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Furthermore, nimodipine has been administered intraarterially as a measure of local vasodilative rescue therapy in cases of symptomatic delayed cerebral vasospasm [ 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…New treatment strategies are needed and have to be carefully evaluated [7,8]. Just one example indicating the potential of machine learning in clinical neuroradiology.…”
mentioning
confidence: 99%